The Effectiveness of Environmentally Based Learning Media in Improving Elementary School Students' Science Learning Outcomes - Riska Riska; Minnah El Widdah; Jetra Viktoria (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
To what extent may environment-based learning media enhance IPAS (Integrated Science and Social Studies) learning outcomes for primary school students? That is the primary issue that our study aims to address. This quantitative research employed a real-world experimental design with a control group paradigm that included both a pretest and a posttest. A class that was taught utilising environment-based media served as the experimental group, while a class that was taught using traditional techniques served as the control group. To analyse the data, we used N-Gain, hypothesis testing, and tests for normality and homogeneity. On average (N-Gain score), the experimental group showed a substantial improvement (0.713), while the control group showed a little improvement (0.510). A hypothesis test with a significance level below 0.05 further demonstrated that the two groups were significantly different from one another. Students' performance in IPAS and the quality of their educational experiences are both enhanced by the usage of environment-based learning tools.